Роль Спецслужб В устранении Неповиновения или Мятежных Действий В Индонезии И Филиппинах (Role of Secret Agent Institutions in Eradication of Rebels In Indonesia and Philippines) - Hapsari, Sekar; Aljihad, Respiratori Saddam (Jurnal Cita Hukum, 2019)
Abstract:A country that has internal problems tends to be faced with problems of its citizens' loyalty and nationalism. There are some citizens in an area of state sovereignty who in fact do group and organized activities against the legitimate government, or make efforts to seize power, or want to be part of an independent region or full autonomy. In order to overcome this, the government established an Intelligence agency (state secret agent) to monitor and spy on and find information about opponents. In Indonesia itself, in several ministries, they have their own intelligence agencies, as well as the Philippines, which has the world's best secret agents. In this paper, the role of Intelligence (secret agent) will be answered in eradicating the insurgency or rebellion movement. This study uses qualitative analysis methods, so it is expected to be able to contribute and input for the next government stakeholders.Keywords: Intelligence, Rebellion, Indonesia, Philippines Abstrak:Negara-negara yang memiliki problem internal Dalam Negeri biasanya dihadapkan pada permasalahan loyalitas dan nasionalisme warganya. Ada sebagaian warga negara dalam suatu wilayah kedaulatan negara yang ternyata malah melakukan kegiatan berkelompok dan terorganisir untuk melawan pemerintahan yang sah, atau melakukan upaya perebutan kekuasaan, atau menginginkan sebagaian wilayah merdeka atau otonomi penuh. Guna mengatasi hal tersebut, maka pemerintah membentuk Lembaga Intelijen (agen rahasia negara) untuk mengawasi dan memata-matai serta mencari informasi pihal lawan. Di Indonesia sendiri di beberapa kementerian telah memiliki lembaga intelijennya sendiri-sendiri, begitu pula halnya dengan Filipina yang ternyata memiliki agen rahasia terbaik dunia. Dalam tulisan ini ingin menjawab peran Intelijen (agen rahasia) dalam memberantas gerakan insurjensi atau pemberontakan tersebut. Penelitian ini menggunakan metode kualitatif analisis, sehingga diharapkan dapat memberikan kontribusi dan masukan bagi pemangku kendali pemerintahan berikutnya.Kata Kunci: Intelijen, Insurjensi, Indonesia, Filipina Аннотация:Страны, имеющие внутренние проблемы, обычно сталкиваются с проблемами лояльности и национализма своих граждан. В государстве существуют граждане, которые фактически проводят групповые и организованные действия для борьбы с законным государством, или пытаются захватить власть всей страны или части независимого региона или отдельной автономии. Для преодоления подобных проблем, государство создало спецслужбу (секретного агента государства) для наблюдения, шпионажа, и поиска информации о противниках. При  нескольких министерствах Индонезии существуют свои спецслужбы, а также они есть в Филиппинах, где работают лучшие в мире секретные агенты. Эта статья посвящена вопросу о том, какую роль играет агентура (секретные агенты) в ликвидации движения неповиновения (мятежных действий). В данном исследовании используется метод качественного анализа. Мы полагаем, Мы полагаем что это исследование поможет внести вклад в познания на данную тему для будущих лидеров государств заинтересованных сторон. Ключевые слова: Разведка, Неповиновение, Индонезия, Филиппины